Effect of adsorption and solvent extraction process on the percentage of carotene extracted from crude palm oil - Latip, R. A.; Baharin, B. S.; Che Man, Y. B.; Rahman, R. A. (Wiley, 2001)
Palm carotene was successfully concentrated from crude palm oil (CPO) by a batch adsorption process using a synthetic (polymer) adsorbent followed by solvent extraction. Carotene was concentrated to about 20,000 ppm, or about 33.3 times the original concentration in CPO. Carotene recovery varied from 16 to 74% depending on the process conditions. Adsorption times, isopropanol (IPA) extraction times, temperatures of adsorption and solvent extraction process, effect of agitation during IPA extraction process, and adsorbent lifespan were evaluated to determine their effects on the percentage of carotene extracted and carotene concentration. The minimum adsorption time required was 0.5 h. However, an adsorption time of 1.5 h gave a significantly higher carotene concentration than adsorption times of 0.5, 1.0, and 0.2 h. The IPA extraction time was determined based on the final carotene concentration desired. The suitable temperature for adsorption and solvent extraction process was 40°C. There was no significant difference in the percentage of carotene extracted and carotene concentration between the IPA extraction process with and without agitation.